A Survey of Off-label and Unlicensed Antibiotic and Respiratory Medications Prescribed for Toddler Patients - Ali Soochi; Ramin Abrishami; Amir Nouroozi; Dariush Taleei (Journal of Pharmaceutical Care, 2022)
Background: Many medications are unlicensed for use in toddlers and many drugs are prescribed as off-label in this age group. Different studies showed high prevalence of prescribing such medications in children. Prescribing off-labeled or unlicensed drugs can cause adverse drug events (ADEs) and harm to the patients. To evaluate the rate of off-label and unlicensed drugs prescribed for toddlers. Methods: Out-patient prescriptions within the electronic database from a main governmental health insurance company in Tehran, Iran were evaluated for off-label and unlicensed drugs in a two-month period (November-December 2019). Results: 5358 prescriptions for toddlers reached to the insurance database, of these, 461 prescriptions were randomly selected. Three hundred and fifty prescriptions contained antibiotics and/or respiratory medications, from them, 183 (52.3%) had at least one off-labeled or unlicensed medication. Conclusion: Our study showed high rates of off-label and/or unlicensed medication use in pediatric population.